Teori Hasil Belajar pada Siswa SDIT Cendikia - Hilwatunnisa Nur Layali; Sarah Sohiah (Pendidikan Islam Anak Usia Dini STIT Palapa Nusantara, 2020)
Student learning outcomes are influenced by many factors, including student interst and learning motivation. Learning outcomes are a number of experiences gained by students who encompass the cognivite realm is the ability of students to work on the problems given. This article discusses the influence of students interest and motivation on learning outcomes in lesson sd in SDIT GLOBAL CENDIKIA. To improve learning outcomes it is necessary to develop a learning method that can improve student activities and learning outcomes through classroom action research. This research method uses data collection in the from of observation. From the analysis of student learning outcomes obtained in the cognitive domain that value of student evaluation questions given by the teacher when the learning process takes place. The results of this study can be used SDIT GLOBAL CENDIKIA to find out the learning styles of student learning outcomes and can be used for considerration of schools and parents of students to improve attention to students, especially those in grades V AND VI.